Mapping the Nexus of Transformational Leadership, Pedagogical Competence, and Learning Management Innovation: A Scoping Review and Its Implications for Islamic Religious Education - Nur Munajat; Muqowim (Jurnal Pendidikan Agama Islam, 2025)
Purpose – This study explores the intersection of transformational leadership, pedagogical competence, and learning management innovation in teacher education. While these constructs have been studied individually, their integration remains underexplored, particularly in the context of Islamic Religious Education (IRE). The purpose of this scoping review is to map existing literature, identify key themes, and highlight implications for developing teacher agency and future-ready pedagogical models in IRE. Design/methods/approach – The review employed Arksey and O’Malley’s scoping review framework, refined by Levac, and aligned with PRISMA-ScR guidelines. A systematic search of the Scopus database (2016–2025) was conducted using Boolean combinations of keywords related to leadership, pedagogy, and innovation in teacher education. Studies that met inclusion criteria were analyzed thematically following Braun and Clarke’s six-phase approach. Findings – From 827 identified records, 33 studies were included, revealing three major themes: (1) transformational leadership works best in collaborative, distributed settings that strengthen teacher agency; (2) pedagogical competence grows through TPACK use, reflective practice, and cultural responsiveness; and (3) learning management innovation is effective when institutionally supported, though often limited by resistance and resource constraints. Overall, teacher agency consistently appears across the reviewed literature as a cross-cutting theme linked to adaptability and innovation, suggesting its relevance for strengthening leadership, pedagogy, and institutional improvement within IRE. Research implications/limitations – This research shows that strengthening teacher agency can guide theoretical development in IRE and inform practical improvements in leadership and pedagogy, though its reliance on a single database and its descriptive scoping design limit the breadth and depth of its conclusions. Originality/value – This paper offers an integrated lens on leadership, pedagogy, and innovation while proposing their contextual relevance for IRE. Embedding teacher agency in IRE can foster reflective, inclusive, and technologically responsive religious educators. The study contributes a foundation for future empirical research on leadership-driven pedagogical innovation in Islamic education.